The effects of economic globalisation and ethnic fractionalisation on redistribution - Regina Pleninger; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2019)
We examine the effect of economic globalisation on income redistribution and hypothesise that it depends on ethnic fractionalisation. In highly fractionalised countries, powerful ethnicities are able to extract globalisation-induced benefits, whereas their governments face substantial political obstacles when redistributing income between ethnic groups. Using the newly constructed KOF Globalisation Index, we find supportive evidence for the interactive effect of ethnic fractionalisation and de jure financial globalisation on redistribution. In particular, the total effect of de jure financial globalisation on redistribution is negative in highly fractionalised countries. Governments in these countries are apparently not only reluctant to offset potential consequences stemming from de jure financial globalisation, but they even reduce redistribution to lower levels.
hdl:20.500.11850/383383
Keywords: D31; D63; F15; O11; O15; 330; Income redistribution; Globalisation; Ethnic fractionalisation